A 60-year expirience in the treatment of pancreatic insulinoma in the Military Medical Academy, Belgrade, Serbia - Tavčar, Ivan; Kiković, Saša; Bezmarević, Mihailo; Rusović, Siniša; Perišić, Nenad; Mirković, Darko; Kuzmić-Janković, Snežana; Dragović, Tamara; Karajović, Jelena; Sekulović, Leposava; Hajduković, Zoran (Vojnosanitetski pregled, 2014)
Background/Aim. Insulinomas are rare benign tumors in the most cases and the most frequent endocrine tumors of the pancreas. A wide spectrum of clinical manifestations in patients with insulinoma is the reason for difficult recognition of the disease with a long period of time between the onset of symptoms and the diagnosis. Diagnostic procedures include Whipple’s triad, 72-hour fast test and topographic assessment. The only currative therapy for patients with insulinoma is operative treatment. Methods. This retrospective study included 42 patients with diagnosis of insulinoma treated in our institution in a 60-year period. In all the patients a demographic and clinical data, types of biochemical methods for diagnosis, and diagnostic procedures for insulinoma localization were analyzed. Tumor size and localization, surgical procedures, postoperative complications and outcome were assessed. Results. A study included 42 patients, 29 women and 13 men. The median age at diagnosis was 43 years. Median time between the onset of symptoms and diagnosis was 3 years. The most common clinical symptoms and signs were disturbance of consciousness and abnormal behavior in 73%, confusion and convulsions in 61% of patients. The diagnosis of insulinoma was estimated by Whipple’s triad and 72-hour fast test in 14 patients. Determination of insulinoma localization was assessed by angiography in 16 (36%) of the patients, by ultrasound (US) in 3 of 16 (18.8%) patients, by abdominal computed tomography (CT) in 8 of 18 (44.5%) patients, and magnetic resonance imaging (MRI) in 2 of 8 (25%) patients. Insulinoma was found in 13 of 13 (100%) patients by arterial stimulation with venous sampling (ASVS) and in 13 of 14 (93%) patients by endoscopic ultrasound (EUS). Of the 42 patients, 38 (90.5%) underwent operative procedure. Minimal resection was performed in 28 (73.6%) of the patients [tumor enucleation in 27 (71%) and central pancreatectomy in one (2.6%) of the patients], and the major resection was performed in 9 (23.6%) of the operated patients [distal splenopancreatectomy in 8 (21%) and pancreaticoduodenectomy in one (2.6%) patient]. The overall mortality rate in postoperative period was 2.6% (one patient). Conclusion. A combination of ASVS and EUS as diagnostic procedures ensures high accuracy for preoperative determination of insulinoma localization. Minimal resection such as enucleation shoud be performed whenever it is possible.